Where is the human in human-centered AI? Insights from developer priorities and user experiences. (April 2023) - Bingley, William J.; Curtis, Caitlin; Lockey, Steven; Bialkowski, Alina; Gillespie, Nicole; Haslam, S. Alexander; Ko, Ryan K.L.; Steffens, Niklas; Wiles, Janet; Worthy, Peter
Abstract: Human-centered artificial intelligence (HCAI) seeks to shift the focus in AI development from technology to people. However, it is not clear whether existing HCAI principles and practices adequately accomplish this goal. To explore whether HCAI is sufficiently focused on people, we conducted a qualitative survey of AI developers ( N = 75) and users ( N = 130) and performed a thematic content analysis on their responses to gain insight into their differing priorities and experiences. Through this, we were able to compare HCAI in principle (guidelines and frameworks) and practice (developer priorities) with user experiences. We found that the social impact of AI was a defining feature of positive user experiences, but this was less of a priority for developers. Furthermore, our results indicated that improving AI functionality from the perspective of the user is an important part of making it human-centered. Indeed, users were more concerned about being understood by AI than about understanding AI. In line with HCAI guidelines, developers were concerned with issues such as ethics, privacy, and security, demonstrating an 'avoidance of harm' perspective. However, our results suggest that an increased focus on what people need in their lives is required for HCAI to be truly human-centered. Highlights: Social impact of AI was a defining feature of users' positive experiences, but this was less of a priority for developers. Functionality of AI was key for both users and developers. AI understandability was less important for users than being understood by AI. Ethics, privacy, and security were considered to be important by developers, but were not key themes of user responses.